2019
DOI: 10.1080/10691898.2019.1677533
|View full text |Cite
|
Sign up to set email alerts
|

Developing Interactive Educational Songs for Introductory Statistics

Abstract: This article describes the process used to develop and assess an NSF-funded instructional innovation: an online collection (https://www.CAUSEweb.org/smiles/) of 28 interactive songs of high esthetic quality designed to span literature-based learning objectives of introductory statistics that develop statistical literacy and reasoning. The interactive songs are also designed to reduce statistics anxiety and require little time or instructor expertise. The songs are interactive in that the interface solicits (an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 30 publications
(24 reference statements)
0
13
1
Order By: Relevance
“…Regarding song length, our evidence that students prefer songs to be as short as possible, perhaps Ͻ30 s, corroborates and extends previous data on this point (8), but seems to be in conflict with the lengths of most educational STEM songs used in high school and college. In a national curated database of 178 songs about statistics (19,21,28), the median song length was found to be 1 min 55 s, i.e., over twice as long as the longest song in the present study, whereas in a database of 191 physics songs (32), the median song length was 2 min 7 s (Fig. 3).…”
Section: Discussioncontrasting
confidence: 46%
“…Regarding song length, our evidence that students prefer songs to be as short as possible, perhaps Ͻ30 s, corroborates and extends previous data on this point (8), but seems to be in conflict with the lengths of most educational STEM songs used in high school and college. In a national curated database of 178 songs about statistics (19,21,28), the median song length was found to be 1 min 55 s, i.e., over twice as long as the longest song in the present study, whereas in a database of 191 physics songs (32), the median song length was 2 min 7 s (Fig. 3).…”
Section: Discussioncontrasting
confidence: 46%
“…To cover many overall basic aspects of regression, including assessing the scatterplot for linearity, predicting Y from x , and interpreting slope and r 2 , there is a song “Regression Rumba” [19] written in that globally popular musical form.…”
Section: Basicsmentioning
confidence: 99%
“…Reflecting on that experiment led to our current NSF grant (Project SMILES) to write and assess songs that are "interactive"-kind of like the Mad Libs TM word game-where students give inputs in advance that end up highlighted in the completed song on the playback page. We detailed our process in the last JSE (Lesser et al 2019), and a 3-min overview video is on our project website: https://www.CAUSEweb.org/ smiles/. Pilot studies at a research university and at a majority Black two-year college showed students found the innovation to help their learning and lower their anxiety.…”
Section: Statistics Education Researchmentioning
confidence: 99%